2014
DOI: 10.1007/s00464-014-3610-y
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of submucosal tumors in muscularis propria: the choice between direct excavation and tunneling resection

Abstract: For SMTs <10 mm, both ESE and STER have satisfactory therapeutic results, it is not necessary to pursue a difficult procedure when a simple method is available. For SMTs >10 mm, STER is a preferable choice in terms of preventing air leakage symptoms, especially, when perforation is likely to happen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 16 publications
0
49
0
Order By: Relevance
“…Wang et al (29) demonstrated that STER has advantages over ESD in terms of promoting a rapid wound healing and reducing the operating time and hospital stay without compromising the success rate or increasing complications. With regard to SMTs > 10 mm, STER is the preferable choice compared with ESE with regard to the prevention of air leakage symptoms (30). However, little is known about how the STER and EFTR procedures compare for the treatment of gastric fundus SMTs.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (29) demonstrated that STER has advantages over ESD in terms of promoting a rapid wound healing and reducing the operating time and hospital stay without compromising the success rate or increasing complications. With regard to SMTs > 10 mm, STER is the preferable choice compared with ESE with regard to the prevention of air leakage symptoms (30). However, little is known about how the STER and EFTR procedures compare for the treatment of gastric fundus SMTs.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, >20 studies have been published with outcome data based on >700 patients (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)22,29,30,(32)(33)(34)(35). In these studies, therapeutic success was recorded for >77% of patients and en bloc resection was achieved in >85% of patients, while irregularly shaped or larger tumors were risk factors in piecemeal resection (33).…”
Section: Efficacy Of Stermentioning
confidence: 99%
“…Lu et al (35) retrospectively analyzed the clinical data of 77 patients with upper gastrointestinal SMTs, 42 of which received STER and 35 of which received ESE, and demonstrated that the efficacy and complications of the two techniques were comparable, though STER decreased air leakage for SMTs by >10 mm compared with ESE. (32) retrospectively evaluated the clinical data of 31 patients with esophageal leiomyoma (diameter, 35-55 mm), 18 of which received STER and 13 of which received VATS, and revealed that the efficacy of the two techniques were comparable, though STER was associated with decreased operation time, a reduced decrease in hemoglobin level, and decreased cost and duration of hospital stay compared with VATS.…”
Section: Comparing Ster and Esd Wang Et Almentioning
confidence: 99%
“…[15][16][17][18][19] However, for multiple SMTs, repeated resections by STER procedure in a different tunnel seems to be a time-consuming effort and make patients suffer too much. In this study, we first focused on using STER technique to resect upper GI multiple SMTs originating from the MP layer.…”
Section: Discussionmentioning
confidence: 99%